An analysis of organic agriculture in Turkey: The current situation and basic constraints - (:unkn) unknown (My University, 2007)
This article gives information about the current situation of Turkish organic agriculture, especially by comparing the official recognition for organic farming in the European Union with that of Turkey and summarizes the existing constraints. The analysis indicates that the further development of Turkish organic agriculture depends upon the development of the domestic organic market and Turkey has to fulfil a number of conditions to provide it. It is needed that the Turkish state both encourages organic production for the domestic market and supports organic agriculture by all means.
Keywords: Domestic organic market; EU; Organic agriculture; Turkey